Self-medication Practices During the Covid-19 Pandemic in a Latin American Country: A Cross-sectional Survey Study. - Salvador-Carrillo, José; Campos-Loza, Luz; Guillen-Carbajal, David; Real-Pantoja, Jakelyn; Pachas, Allison; Crisol-Deza, Diego; Saravia, Luis; Rey-Vidal, Oliver; Usquiano-Cardenas, Luis; Flores, Claudio; Izaguirre, Víctor; Zevallos, Alejandra; et al. (Inquiry (00469580), 2024)
The COVID-19 pandemic has led many people to turn to self-medication as an accessible and convenient method of managing their health. Thus, this study sought to describe the self-medication practices (SMP) and their risk factors among the Peruvian population during the COVID-19 outbreak. A cross-sectional study was conducted from January to March, 2021, in 3 cities of Peru (Lima, Ica, and Chincha). An e-survey was distributed virtually to these populations. The association among the SMP and other variables was explored using the Chi-square test and then analyzed by the Poisson regression model (step-wise). The degree of association was represented by a prevalence ratio (PR) with its respective 95% confidence interval (95% CI). A total of 2207 participants (38.86 ± 15.1 yo) were included. 70.1% (n = 1547) were women and 70.0% (n = 1544) were from Lima. The frequency of SMP among all participants was 35.93%. In the self-medicated population, the most used drugs without a prescription were ivermectin (drops, 72.01%, n = 571), paracetamol (41.24%, n = 327), and azithromycin (25.81%, n = 284). The main factors associated with SMP were living in Chincha (P <.001; PR:1.44; 95% CI: 1.26-1.65), being divorced or widowed (P =.002; PR: 1.37; 95% CI: 1.27-1.93), being an informal employee (P <.001; PR:1.45; 95% CI: 1.23-1.71), and having symptoms of SARS-CoV-2 infection with no confirmed diagnosis (P <.001; PR: 2.17; 95% CI: 1.88-2.50). Our results showed that more than a third of all our participants self-medicated themselves. The SMP was associated mainly with residing in Chincha, not having any marital status, being informally employed, and having the presence of symptoms related to COVID-19 without diagnosis.